The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/1055665619883155
|View full text |Cite
|
Sign up to set email alerts
|

Photogrammetric Evaluation of Soft Tissue Profile and Frontal Photographs in Repaired Bilateral Cleft Lip and Palate

Abstract: Objective: To evaluate the soft tissue profile and frontal photographs of 8- to 12-year-old patients with repaired complete bilateral cleft lip and palate (BCLP). Methods: The profile and frontal photographs obtained from 31 nonsyndromic BCLP children (aged 8-12 years: 14 boys and 17 girls) were analyzed and compared with an age- and sex-matched normal population (18 boys and 32 girls). In each patient, 12 soft tissue angular and proportional parameters on the frontal photograph and 12 angular parameters for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
3
0
1
Order By: Relevance
“…Similar results were found in previous soft tissue profile analysis of subjects with complete cleft lip and palate. 12 In contrast, Lin et al reported normal facial convexity in fifty subjects with unoperated unilateral cleft palate compared with noncleft controls by measuring facial profile photographs. 3 This difference might be a result of the different measurement techniques used.…”
Section: Discussionmentioning
confidence: 96%
“…Similar results were found in previous soft tissue profile analysis of subjects with complete cleft lip and palate. 12 In contrast, Lin et al reported normal facial convexity in fifty subjects with unoperated unilateral cleft palate compared with noncleft controls by measuring facial profile photographs. 3 This difference might be a result of the different measurement techniques used.…”
Section: Discussionmentioning
confidence: 96%
“…It has been shown that patients who have undergone a cleft lip and/or palate repair still exhibit certain soft-tissue deformities when compared with a control group, particularly in the nasofrontal region. 30 The facial shape of unaffected parents who have children with cleft lip and palate has also been shown to display significant differences compared to the general populations. 31 Understanding whether these variations occur more often in different ethnicities or subpopulation groups may help further classify treatment options depending on a patient's ethnic origin and stratify service provision, and be extrapolated to all other aspects of congenital deformity and reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Отримані результати є співзвучними з аналогічними дослідженнями деяких авторів [17], які встановили виражені відмінності у структурі назо-…”
Section: антропометричні особливості обличчя у дітей з уродженими деф...unclassified